Studi Kasus Gangguan Clumsiness Anak Kelompok A di TK Children Centre Brawijaya Smart School : Case Study of Clumsiness Disorder of Group A Children at Children's Centre Kindergarten Brawijaya Smart School - Wilda Isna Kartika; Febry Maghfirah (Sam Ratulangi University, 2023)
There are still many parents who don't know that a child's fine and gross motor skills need to be trained and developed all the time through various daily activities. The aim of this research is to determine the characteristics of clumsiness, how to handle clumsiness, and the obstacles experienced by teachers in dealing with clumsiness. The results of a preliminary study on children Group A at Children Centre Brawijaya Smart School, there were children who appeared to have difficulty carrying out fine motor activities, for example, writing, drawing, or self-help activities, for example, dressing, buttoning shirts or trousers. This research used a qualitative approach. The type of research used is case study research. The subject of this research was a child with the initials DF who studied at the Children Center Brawijaya Smart School. The data collected techniques used were observation, interviews, and documentation. This research used data analysis techniques with an interactive model according to Miles and Huberman which consists of four stages, data collection, data reduction, data presentation, and conclusion. The research showed that children still need help carrying out these activities. The teacher's method of handling provides motivation and opportunities for children to try. The obstacles experienced by teachers in overcoming them are that children often say